1997
DOI: 10.1002/(sici)1097-0142(19970101)79:1<12::aid-cncr3>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced induction of apoptosis of human gastric carcinoma cells after preoperative treatment with 5-fluorouracil

Abstract: The authors demonstrated enhanced apoptosis in gastric tumors after continuous intravenous infusion of 5-FU for 7 days. This result suggests that it may be possible to evaluate the effects of chemotherapy by detecting apoptotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…However, there are several possible explanations: 1) 5-FU is known to induce apoptosis in gastric cancer xenografts in a concentration-dependent manner. 33,34) The anti-cancer drug can reportedly penetrate tumor tissue only 100-250 µm from the surface, which might be sufficient, at least in part, for the treatment of omental micrometastases with a diameter of less than 0.5 mm, but not for more advanced metastasis of larger size. 35) Therefore, preferential inhibition of peritoneal metastasis may be due to higher apoptosis induced by a higher concentration of 5-FU in the micrometastatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several possible explanations: 1) 5-FU is known to induce apoptosis in gastric cancer xenografts in a concentration-dependent manner. 33,34) The anti-cancer drug can reportedly penetrate tumor tissue only 100-250 µm from the surface, which might be sufficient, at least in part, for the treatment of omental micrometastases with a diameter of less than 0.5 mm, but not for more advanced metastasis of larger size. 35) Therefore, preferential inhibition of peritoneal metastasis may be due to higher apoptosis induced by a higher concentration of 5-FU in the micrometastatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are summarized as follows: (i) a higher apoptotic index (AI; percentage of apoptotic tumor cells) in tubular adenomas, followed by welldifferentiated (intestinal-type), and poorly differentiated (diffuse-type) carcinomas [1][2][3], (ii) lower AI in carcinomas expressing P53 oncoprotein [3,4], (iii) increase in AI with preoperative chemotherapy [5], (iv) association of thymidine phosphorylase expression with lower AI [6], and (v) an inverse correlation between AI and intratumoral microvessel density (IMVD) [6]. Thus, apoptosis is correlated with tumor histology, p53 gene status, and cytotoxic agents such as anticancer agents, as well as being correlated with blood supply.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed apoptosis played a main role in the prevention and treatment of tumors [11][12][13] . Anti-tumor effect of many chemotherapy drugs could induce apoptosis in tumor cells [14,15] . Cell apoptosis was regulated by genes [16,17] .…”
Section: Discussionmentioning
confidence: 99%